2008
DOI: 10.1007/s10310-007-0050-8
|View full text |Cite
|
Sign up to set email alerts
|

Estimating understory vegetation response to multi-nutrient fertilization in Douglas-fir and ponderosa pine stands

Abstract: Models were developed to predict understory vegetation response to multi-nutrient fertilization at six conifer-forested stands in the inland Northwest United States. Equations are presented to estimate how fertilization as well as other factors impacting understory production in the inland Northwest change total understory vegetation production and the production of three individual lifeforms (shrubs, forbs, and grasses and grasslikes). Overstory stand density was found to have the greatest impact on understor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…In this study, both UVSN and stand timber volume increased with rising tree density until a certain threshold; thereafter, the stand timber volume increased continuously but the USVN decreased (Figure ). This is similar to other studies (Barbier et al, ; Bohn & Huth, ; VanderSchaaf, ).…”
Section: Discussionsupporting
confidence: 93%
“…In this study, both UVSN and stand timber volume increased with rising tree density until a certain threshold; thereafter, the stand timber volume increased continuously but the USVN decreased (Figure ). This is similar to other studies (Barbier et al, ; Bohn & Huth, ; VanderSchaaf, ).…”
Section: Discussionsupporting
confidence: 93%
“…The coefficient of tree density in the regression equation of the Shannon-Wiener index was −0.336, indicating that tree density was negatively correlated with species diversity in the herbaceous layer. Some studies also found that the number of understory vegetation species increased with rising tree density until a certain threshold [15,33]. The main reason is that when the tree density exceeds the ideal density, a competitive situation between stands forms for subsistence resources, which inhibits the growth and development of understory vegetation, resulting in a decrease in diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Water and nutrient fertilization are equally indispensable for plant seed formation and development [43]. Plant roots absorb nutrients from the soil, which is rich in minerals and organic matter to feed seed formation.…”
Section: Water and Nutrient Fertilizationmentioning
confidence: 99%